(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The choice of one package or the other can be an economic decision or can be influenced by cultural acceptance or perception of individual convenience. Product package systems can be designed for onetime use or multiple-use purposes. Package perceptions in different countries typically develop from a variety of factors, including climate, lifestyle, and cultural acceptance with regard to particular products.In an increasingly global economy with multinational firms marketing products worldwide, it is important to understand the differences between consumer needs and consumer responses to product-package systems. The importance of packaging design and the role of packaging as a vehicle for consumer communication and branding are necessarily growing. To achieve communication goals effectively, knowledge about consumer psychology is important so that manufacturers understand consumer response to their packages.